2022
DOI: 10.1111/famp.12821
|View full text |Cite
|
Sign up to set email alerts
|

Examining the stability of emotional regulation and psychological distress for low‐income individuals: A latent transition analysis

Abstract: Previous relationship education research has focused on investigating healthy relationships at the couple level, with limited research conducted on individual‐oriented relationship education programs for economically disadvantaged individuals. More specifically, there is a lack of research on how individual‐oriented relationship education programs contribute to changes in unique attributes of individuals who enroll in these programs and who would benefit most from relationship education programs. The primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Le et al (2023) examined low-income couples receiving one of two online relationship interventions compared to a waitlist control and found that men and women in the intervention condition were more likely to be in a group that achieved large improvement over time relative to the control group. Taylor et al (2023) examined individuals participating in a relationship education program compared to a waitlist control and found that those in the intervention group were more likely to transition to a group with better individual functioning. Together, these studies offer important early evidence that change patterns among those receiving CRE can differ from controls.…”
Section: The Prosaaf Interventionmentioning
confidence: 99%
“…Le et al (2023) examined low-income couples receiving one of two online relationship interventions compared to a waitlist control and found that men and women in the intervention condition were more likely to be in a group that achieved large improvement over time relative to the control group. Taylor et al (2023) examined individuals participating in a relationship education program compared to a waitlist control and found that those in the intervention group were more likely to transition to a group with better individual functioning. Together, these studies offer important early evidence that change patterns among those receiving CRE can differ from controls.…”
Section: The Prosaaf Interventionmentioning
confidence: 99%
“…However, collectively, they represent one's ability for distress tolerance, or to stay regulated when stressed. Individuals who can regulate emotions during challenging conversations are able to maintain healthier psychological distress and consequently, more positive relationships (Dillman Taylor et al, 2022). Additionally, we chose to focus on these three constructs because we found positive intervention effects at 1‐month follow‐up postrandom asignment for individual distress, 6‐month follow‐up for emotion regulation and stress communication in the primary outcome analysis (see Barden et al, 2022).…”
Section: The Current Studymentioning
confidence: 99%